Human Resource Development Strategy in Improving Service Excellent - Agsal, A. Asih Yustiana; Djabar, Sadly Abdul; Suyuti, Nurmadhani Fitri (Journal of Management and Administration Provision, 2023)
This research aims to find out the Human resource development strategy in improving Service Excellent at PT. Penjaminan Kredit Daerah (Jamkrida) South Sulawesi, a Regional Owned Enterprise of the South Sulawesi Provincial Government. This research was conducted at PT. Penjaminan Kredit Daerah (Jamkrida) South Sulawesi. The data used were primary data and secondary data. Data collection was done through observation, interview, and documentation techniques. The data that has been collected is then processed and analyzed descriptively through the stages of data reduction, data presentation, and conclusion drawing. The results of this study indicate that to improve Service Excellent at PT. Penjaminan Kredit Daerah (Jamkrida) South Sulawesi, HRD conducts regular training and development to improve service quality so that it is expected to satisfy customers / prospective customers. Training and development of human resources carried out by PT. Penjaminan Kredit Daerah (Jamkrida) South Sulawesi include service excellence training or excellent service which aims to provide the best service to customers/prospective customers and socialization of consumer complaint resolution in Financial Services Business Actors. Good complaint handling will increase consumer confidence, which in turn can also increase consumer loyalty. In the end, customer loyalty will increase the company's revenue potential (profitability). It can be concluded that providing training to employees is the main strategy carried out by the HRD of PT. Penjaminan Kredit Daerah (Jamkrida) South Sulawesi, to increase service excellent and work productivity.